Battery‐Less Motion Sensing: A Battery‐Less Arbitrary Motion Sensing System Using Magnetic Repulsion‐Based Self‐Powered Motion Sensors and Hybrid Nanogenerator (Adv. Funct. Mater. 36/2020). (3rd September 2020) - Bhatta, Trilochan; Maharjan, Pukar; Salauddin, Md.; Rahman, M. Toyabur; Rana, SM Sohel; Park, Jae Yeong
Abstract : In article number 2003276, Jae Yeong Park and co‐workers successfully demonstrate a battery‐less arbitrary motion sensing system based on magnetic repulsion, which integrates four self‐powered motion sensors and a hybridized nanogenerator as an eco‐friendly power source on a single device. This integrated system can efficiently sense, process, and transmit the motion data wirelessly and could serve future autonomous control systems for intelligent networking.